Surface chemistry modification of glass and gold for low density neural cell culture - Albutt, Darren James (2013)
Surface chemical modifications are presented for supporting primary neurons in culture. The initial substrates for culture were glass and gold. The surface modifications were based on self assembled monolayer (SAM) approaches. Glass surfaces were initially modified by silanisation with either 3-aminopropyltrimethoxysilane (APTMS) or 3-aminopropyldimethylethoxysilane (APDES), to present amino-terminated surfaces. Gold surfaces were initially modified by thiol SAMs of either 11-amino-1-undecanethiol (AUT) or a peptide fragment of laminin (PA22-2), to present an amino- or peptide-terminated surface respectively.